The AI-Augmented Physician: How Artificial Intelligence is Transforming Daily Medical Practice - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The AI-Augmented Physician: How Artificial Intelligence is Transforming Daily Medical Practice The integration of Artificial Intelligence (AI) into heal...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation